Validity of Thyroid Ultrasound in Diagnosing Malignancy in Thyroid Nodule - Kundi, Sana; Jabeen, Mahwish; Rafique, M. Salman; Rehman, M. Atiq U; Safi, Abdullah; Amin, M.; Umer, U. Siddique; Alam, Shahjehan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the validity of ultrasound in the diagnosis of malignant thyroid nodule keeping histopathology as gold standard. Methodology: This was a cross sectional study conducted in Radiology department of a Tertiary care Hospital, Islamabad for a period of one year. In this study, 55 patients who presented to indoor and outdoor department of hospital with palpable thyroid nodules underwent USG. The results of ultrasound were then compared with histopathological findings. Result: Out of 55 patients, on the basis of ultrasound, 5 male cases with thyroid nodule were malignant and 9 were benign while 8 females were malignant and 33 benign. But on histopathology report, out of 5, only 3(21%) males had malignancy while in females, 7(17%) out of 8 found malignant. 9 patients were true positive for malignancy and 4 patients were false positive, 41 patients were true negative for malignancy and one was false negative. Sensitivity was 90% while specificity was 91.1%. Positive predictive value was 69.2% and negative predictive value was 97.6%. Conclusion: Thyroid ultrasound is a valuable diagnostic tool in predicting malignancy in thyroid nodules with sensitivity of 90% and specificity of 91.1%.